Effectiveness of therapeutic interventions for women with urinary incontinence: A systematic review - Shamima Islam Nipa (2020)
© 2020 by Begell House, Inc. Background: Urinary incontinence is a common condition that reduces the quality of life of women specifically. To reduce this problem, it is necessary to identify the best possible therapeutic options. Purpose: To synthesize the evidence on effective therapeutic options for women with urinary incontinence. Data Sources: We extracted relevant papers from the Hinari, PubMed, Cochrane, Science Direct, Embase, PEDro, and Cinahl databases. Several studies were searched comprehensively. Study Selection: We integrated data from 17 randomized controlled trials related to therapeutic interventions for the management of urinary incontinence in women. Data Extraction: The PEDro scale was used to grade the level of evidence. The contents and outcomes of different therapeutic interventions for various types of urinary incontinence were explored. Data Synthesis: The comparative effectiveness of the interventions was analyzed based on intervention and control groups, long-term follow-up, adequate sample size, and intention to treat analyses. The primary outcomes of the studies considered reduced severity of urinary incontinence and secondary outcomes such as satisfaction, improved self-esteem, sexual function, and quality of life. Conclusions: Our findings suggest that pelvic-floor muscle exercise, behavioral training, electrical stimulation, vaginal cones, whole-body vibration treatment, and modified Pilates are significantly effective at reducing urinary incontinence. Nevertheless, persisting with one of these intervention procedures is difficult. Therefore, we recommend further study for long-term follow-up.